Verification, Model Checking, and Abstract Interpretation 14th International Conference, VMCAI 2013, Rome, Italy, January 20-22, 2013. Proceedings - Giacobazzi, Roberto; Berdine, Josh.; Mastroeni, Isabella; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 14th International Conference on Verification, Model Checking, and Abstract Interpretation, VMCAI 2013, held in Rome, Italy, in January 2013, co-located with the Symposium on Principles of Programming Languages, POPL 2013. The 27 revised full papers presented were carefully reviewed and selected from 72 submissions. The papers cover a wide range of topics including program verification, model checking, abstract interpretation and abstract domains, program synthesis, static analysis, type system, deductive methods, program certification, debugging techniques, program transformation, optimization, hybrid and cyber-physical systems.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Software Engineering; Computer Communication Networks; Mathematical Logic and Formal Languages; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).